The Impact of a Comprehensive Simulation-Based Training and Certification Program on Resident Central Venous Catheter Complication Rates. Issue 2 (April 2021) - Day, Jonathan; Winchester, Zachary B.; Cairns, Cassandra A.; Goyal, Munish; Kumar, Anagha; Bell, Jacob; Katz, Jared; Fitzgibbons, Shimae C.
Abstract : Introduction: Millions of central venous catheters (CVCs) are placed annually in the United States, many by resident physicians. Simulation training has been proposed as a means to increase resident physician competence with CVC placement and decrease the incidence of line-associated mechanical complications. We aimed to evaluate the impact of a novel simulation-based CVC training program for resident physicians on CVC-associated mechanical complication rates. We hypothesized that the CVC-related mechanical complication rates would be lower among simulation-trained residents (STRs) compared with nonsimulation, traditionally trained residents (TTRs). Methods: A retrospective chart review was performed of patients with a CVC placed by a resident physician between October 2014 and January 2017 at MedStar Georgetown University Hospital in Washington, DC. Incidence of CVC mechanical complications, including pneumothorax, hemothorax, arterial injury, or retained guidewire, were extracted from the electronic medical record and compared between STR and TTR cohorts. In contrast to TTRs who were trained to place CVCs in a supervised clinical setting, STRs underwent a CVC training program using online modules, a hands-on simulation training and testing checklist, and a series of successful supervised insertions before being credentialed to place lines independently. Results: Nine hundred twenty-four CVCs placed by resident physicians during the study period were analyzed. There was no statistically significant difference in total mechanical complication rates between the STRs and TTRs in this study period (2.4% vs. 2.2%, P = 1). Simulation-trained residents were more likely to use ultrasound guidance when indicated during CVC insertion compared with TTRs (94.8% vs. 70.5%, P < 0.001). Conclusions: Mechanical complication rates associated with CVC insertion were similar between the simulation and TTRs and were consistent with previously published literature. These findings suggest that residents who underwent simulation training and certification demonstrated performance on par with more experienced TTRs. In addition, they were more likely to use best practices including ultrasound guidance in line placement. Abstract : Supplemental digital content is available in the text.